A practical guide to e-journal and e-book supply – a UK perspective. Issue 1 (11th February 2014) - Kluzek, Mark
Abstract : Purpose: – The purpose of this paper is to report on current interlending and document delivery of e-books and e-journals in the UK and analyse the challenges encountered in such practices, using the experiences at King's College London as an example. Design/methodology/approach: – The author uses a case study approach. Findings: – Most UK libraries and higher education institutions negotiate the usage terms for their e-resources through Jisc's NESLI2 model license agreement. While the terms of this agreement work relatively well for document delivery of e-journal articles, allowing for secure electronic document transmission under prescribed circumstances, the interlending of e-books remains problematic. Research limitations/implications: – The paper provides insight into how UK document supply services can better use electronic holdings to offset the costs of requesting. It discusses the dilemma of e-books and potential solutions. Practical implications: – This will enable UK library professionals to better use e-resources in a legally compliant way for the purpose of document delivery. It will explain to non-UK library professionals how supplying from e-resources works in the UK. Originality/value: – The paper provides insight into how UK document supply services can better use electronic holdings to offset the costs of requesting. It discusses the dilemma of e-books and potential solutions.